Medial Clamp Tine Positioning Affects Ankle Syndesmosis Malreduction. Issue 8 (August 2017) - Cosgrove, Christopher T.; Putnam, Sara M.; Cherney, Steven M.; Ricci, William M.; Spraggs-Hughes, Amanda; McAndrew, Christopher M.; Gardner, Michael J.
Abstract : Objectives: To determine whether the position of the medial clamp tine during syndesmotic reduction affected reduction accuracy. Design: Prospective cohort. Setting: Urban Level 1 trauma center. Patients: Seventy-two patients with operatively treated syndesmotic injuries. Intervention: Patients underwent operative fixation of their ankle syndesmotic injuries using reduction forceps. The position of the medial clamp tine was then recorded with intraoperative fluoroscopy. Malreduction rates were then assessed with bilateral ankle computerized tomography. Main Outcome Measurement: Fibular position within the incisura was measured with respect to the uninjured side to determine whether a malreduction had occurred. Malreductions were then analyzed for associations with injury pattern, patient demographics, and the location of the medial clamp tine. Results: A statistically significant association was found between medial clamp position and sagittal plane syndesmosis malreduction. In reference to anterior fibular translation, there was a 0% malreduction rate in the 18 patients where the clamp tine was placed in the anterior third, a 19.4% malreduction rate in the middle third, and 60% malreduction rate in the posterior third ( P = 0.006). In reference to posterior fibular translation, there was a 11.1% malreduction when clamp placement was in the anterior third, a 16.1% malreduction rate in the middle third, and 60% malreduction rate in the posterior third ( P = 0.062). There were no significant associations between medial clamp position and coronal plane malreductions (overcompression or undercompression) ( P = 1). Conclusions: When using reduction forceps for syndesmotic reduction, the position of the medial clamp tine can be highly variable. The angle created with off-axis syndesmotic clamping is likely a major culprit in iatrogenic malreduction. Sagittal plane malreduction appears to be highly sensitive to clamp obliquity, which is directly related to the medial clamp tine placement. Based on these data, we recommend placing the medial clamp tine in the anterior third of the tibial line on the lateral view to minimize malreduction risk. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.